Ultrastructural Analysis of the Human Lens Fiber Cell Remodeling Zone and the Initiation of Cellular Compaction - Costello, M. Joseph (2013)
The purpose is to determine the nature of the cellular rearrangements occurring through the remodeling zone (RZ) in human donor lenses, identified previously by confocal microscopy to be about 100 µm from the capsule. Human donor lenses were fixed with 10% formalin followed by 4% paraformaldehyde prior to processing for transmission electron microscopy. Of 27 fixed lenses, ages 22, 55 and 92 years were examined in detail. Overview electron micrographs confirmed the loss of cellular organization present in the outer cortex (80 µm thick) as the cells transitioned into the RZ. The transition occurred within a few cell layers and fiber cells in the RZ completely lost their classical hexagonal cross-sectional appearance. Cell interfaces became unusually interdigitated and irregular even though the radial cell columns were retained. Gap junctions appeared to be unaffected. After the RZ (40 µm thick), the cells were still irregular but more recognizable as fiber cells with typical interdigitations and the appearance of undulating membranes. Cell thickness was irregular after the RZ with some cells compacted, while others were not, up to the zone of full compaction in the adult nucleus. Similar dramatic cellular changes were observed within the RZ for each lens regardless of age. Because the cytoskeleton controls cell shape, dramatic cellular rearrangements that occur in the RZ most likely are due to alterations in the associations of crystallins to the lens-specific cytoskeletal beaded intermediate filaments. It is also likely that cytoskeletal attachments to membranes are altered to allow undulating membranes to develop.